1983
DOI: 10.1095/biolreprod29.2.446
|View full text |Cite
|
Sign up to set email alerts
|

Time Course of the Luteinizing Hormone Surge in Cannulated Rats: Quantitative Variance Estimates Within Individual Rats over Successive Cycles,2

Abstract: The present study was designed to compare quantitative variance estimates in the profile of the luteinizing hormone (LH) surge within individual rats over successive proestrous (PE) days (WITHIN) with the variability between rats (BETWEEN). Sprague-Dawley female rats were implanted under ether anesthesia with indwelling intracardiac cannulas. On successive PE afternoons of normal 4-day cycles, hourly blood samples (0.25 ml) were collected via the cannula from 1400-2000 h for radioimmunoassay of plasma LH. Thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1988
1988
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Previous studies by Carillo and Sawyer [9] and Barofsky and Harney [1] have established that within individual ani mals the time of onset and the time of peak of the LH surge are very consistent over successive cycles. In this study we have confirmed these results, and also established that the time of onset and amplitude of the surge in plasma PRL is very consistent within individual animals on successive proestrous afternoons.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Previous studies by Carillo and Sawyer [9] and Barofsky and Harney [1] have established that within individual ani mals the time of onset and the time of peak of the LH surge are very consistent over successive cycles. In this study we have confirmed these results, and also established that the time of onset and amplitude of the surge in plasma PRL is very consistent within individual animals on successive proestrous afternoons.…”
Section: Discussionmentioning
confidence: 91%
“…Schematic drawing, according to Konig and Klippel [22] and Paxinos and Wat son [29], illustrating the location and the ex tent of AMPO. SC'N and combined AMPO/ SCN lesions (shaded area in frames [1][2][3][4]. AC = Anterior commissure: AH = anterior hypothalamus: AMPO = anterior medial preoptic nucleus [29]: AR = arcuate nucleus; DB = diagonal band: f = fornix: MPA = medial preoptic area: OC = optic chiasm: RCH = retrochiasmatic area: re = nucleus reuniens; SCN = suprachiasmatic nucleus: VMH = ventromedial nucleus.…”
Section: Ampomentioning
confidence: 99%
See 2 more Smart Citations
“…These can then be excluded from further experimentation and analysis. Studies by others that examined the reproducibility of the proestrous LH surge in intact females showed that the timing, but not the magnitude of the LH surge was consistent over successive cycles [58, 59]. It was suggested that this consistency in the timing might reflect the regularity of the circadian clock.…”
Section: Discussionmentioning
confidence: 99%